Training On Innovation In Processing Cassava Into Fish Siomay Dimsum As An Effort To Improve The Economy Of The Mojowuku Village Community, Gresik Regency - Al-Ayubi, Sholihudin; Sirojuddin, Akhmad; Suhartining, Suhartining; Irfani, M Miftakhul; Munandar, M Aris; Lail, Zulfatul (LPPM, STAI Al-Azhar Menganti, 2023)
Mojowuku Village is an agricultural village that has abundant natural resource potential of cassava, but it has not been processed optimally so that it can improve the community's economy in the future. Based on these problems and potential, the community service team (PKM) of the Al Azhar Menganti Institute provided assistance through training in processing cassava into fish dumpling dimsum in the village of Mojowuku Kedamean Gresik. The method used is ABCD (Asset Based Community Development) with (5) five stages, including: First discovery. Second, dream (dream). Third, design (designing). Fourth, define (determine the topic). Fifth, destiny (doing and controlling). The subject of assistance is the PKK women's community in Mojowuku Kedamean Village. The impacts of mentoring felt by the community include: 1. increasing the skills and knowledge of PKK women in entrepreneurship using cassava. 2. increasing family economic income, 3. Reducing the unemployment rate in the village environment. 4. Strengthen the role of the PKK as an institution for empowering women in Mojowuku village